2015
DOI: 10.5604/12321966.1185787
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cyclin A and B1 immunostaining in papillary thyroid carcinoma

Abstract: Introduction and objectives. Cyclin A, encoded by CCNA (cyclin A) gene with locus in chromosome 4q27, and cyclin B1, encoded by CCNB1 (cyclin B1) gene with locus in chromosome 5q12, are proteins that play a key role in the passage through the restriction point in G2 phase of the cell cycle. The aim of the study was to analyse immunohistochemically the expression of cyclins A and B1 in different variants of papillary thyroid carcinoma (PTC). Material and methods. The immunostaining patterns of the proteins in q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The LINC00968/miR-9-3p/CCNA2 regulatory axis was a newly discovered regulatory mechanism in lung adenocarcinoma [26]. A previous study has shown that the expression of Cyclins A and B1 in thyroid papillary carcinoma may have specific immunostaining [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LINC00968/miR-9-3p/CCNA2 regulatory axis was a newly discovered regulatory mechanism in lung adenocarcinoma [26]. A previous study has shown that the expression of Cyclins A and B1 in thyroid papillary carcinoma may have specific immunostaining [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cyniak-Magierska et al revealed that the expression of cyclin B1 in papillary thyroid carcinoma may have a specific immunostaining pattern. If the results are confirmed in a larger patient population, the diagnostic panel constructed with antibodies to these proteins can improve diagnostic accuracy in papillary thyroid carcinoma cases [27]. Sabbaghi et al reported that single-agent trastuzumab emtansine therapy induced by cyclin B1 was used as a pharmacodynamics predictive index for HER2-positive breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the cell cycle-related genes CCNA and CCNB are essential for G1-S phase transition promoting mitosis. Cyclin, as a shared domain of PBK with CCNA and CCNB, can control proliferation and cell cycle progression through the S phase to the G2/M checkpoint by activating cyclin-dependent kinase (Cyniak-Magierska et al 2015). Accordingly, we speculated that the specific mechanism of PBK involved in OC could be that it regulated the cell-cycle process by interacting with the key proteins in the cell-cycle signaling pathway, affecting cell cycle arrest, DNA repair, autophagy, cytokinesis, cell proliferation and cell death, thereby promoting the malignant behaviors of OC cells and ultimately leading to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, about 34% WT showed cyclin A overexpression, defined as increased level of cyclin A comparing with normal kidney tissue. Cyclin A overexpression was found in different human tumors in adults (Aaltomaa et al, 1999; Poikonen et al, 2005; Sørby et al, 2012; Cyniak-Magierska et al, 2015), as well as in pediatric embryonal tumors (Moschovi et al, 2011) and in neuroblastoma tumor NI65 (Molenaar et al, 2003). In contrast, Wang et al (1996) reported decreased expression of cyclin A in colon cancer compared to normal colon mucosa in 63% cases.…”
Section: Discussionmentioning
confidence: 99%